2020
DOI: 10.1093/jrs/feaa009
|View full text |Cite
|
Sign up to set email alerts
|

Syrian Refugees in Canada and Transculturalism: Relationship between Media, Integration and Identity

Abstract: The process of integration of Syrian newcomers into Canada is multifaceted. The Canadian government, in its efforts to welcome refugees, has provided services that smooth this process over on many fronts. While financial and support services are essential to feelings of comfort, safety and security, feelings of identity and belonging constitute a never-ending process. In a globalized world, country of residence can easily change, but attachment to issues in the country of origin enlists a much more complex rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Overall, participants' narratives in our study seem to deconstruct the common portrayal of refugees as a-historical subjects, helpless, passive dependants with limited ability for agency (Ghorashi, 2005;Malkki, 1996;Mcmahon et al, 2016), as well as the "deficit model" which emphasizes vulnerability and trauma (Bogic et al, 2015;Papadopoulos, 2002) at the expense of positive adaptation, coping strengths and resilience in refugee lives (Mohamed & Bastug, 2021;Hutchinson & Dorsett;Shneikat & Ryan, 2017). Biographical interviews facilitated Syrian refugees who found temporary refuge in Greece to articulate their life stories, socio historical circumstances and specific needs, as active responsible, competent, selfdetermined agents.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Overall, participants' narratives in our study seem to deconstruct the common portrayal of refugees as a-historical subjects, helpless, passive dependants with limited ability for agency (Ghorashi, 2005;Malkki, 1996;Mcmahon et al, 2016), as well as the "deficit model" which emphasizes vulnerability and trauma (Bogic et al, 2015;Papadopoulos, 2002) at the expense of positive adaptation, coping strengths and resilience in refugee lives (Mohamed & Bastug, 2021;Hutchinson & Dorsett;Shneikat & Ryan, 2017). Biographical interviews facilitated Syrian refugees who found temporary refuge in Greece to articulate their life stories, socio historical circumstances and specific needs, as active responsible, competent, selfdetermined agents.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…Papadopoulos (2002) emphasized that the usual conceptualisation of refugees is in terms of trauma theories and within a "pathology, symptom-based or deficit model", which articulates a medicalised "trauma discourse" vis-a-vis their mental health. A greater focus on resilience and positive factors of adaptation among refugee people is thus necessary both in theoretical conceptualizations, related research and practice (Mohamed & Bastug, 2021;Hutchinson & Dorsett, 2012).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Studies have also demonstrated this by showing how people's preference for media can be closely associated with their ethnolinguistic identity (Harwood & Vincze, 2015), racial identity (Schieferdecker, 2017), partisan identity (Wischnewski & Krämer, 2020), and national identity (Wojcieszak & Garrett, 2018). Social identity theory has been particularly useful for understanding media choice in minority populations such as Latinos in the United States (Salzman, 2014) and Syrian refugees in Canada (Mohamed & Bastug, 2020). Recent research has also demonstrated links between self-A THEORY OF NEWS READING PUBLICS 14 identity and perception of the media people consume (Schulz et al, 2020) which in turn could influence their media consumption patterns For many Indian citizens, who also strongly identify with their respective states by virtue of their cultural upbringing, it is easy to see why they would take on two roles as news consumers: the first being a consumer of regional news, and the second, being a consumer of national news.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Since the Civil War, more than 5 million Syrians have been resettled in neighboring countries such as Turkey, Lebanon, Jordan, and Iraq, and around 1 million Syrians sought asylum in European countries (Connor, 2018). Canada has accepted approximately 52,000 Syrian refugees (Connor, 2018) and implemented more inclusive policies (Mohamed and Bastug, 2020), while this number in the US remained around 22,000 (Refugee Processing Center, 2020). In the US, the top States that accepted Syrian refugees are California (n = 2,487), Michigan (n = 2,323), and Texas (n = 1,649) (see Table 1 for the numbers in all States; Refugee Processing Center, 2020).…”
Section: The Syrian Refugee Crisis and The Paris Attacksmentioning
confidence: 99%